Tuning the Catalytic Performance of Novel Composites Based on ZIF‐8 and Nafen through Dimensional and Concentration Effects in the Synthesis of Propylene Glycol Methyl Ether. Issue 26 (7th June 2019) - Timofeeva, Maria N.; Paukshtis, Evgeniy A.; Panchenko, Valentina N.; Shefer, Kristina I.; Isaeva, Vera I.; Kustov, Leonid M.; Gerasimov, Evgeniy Yu.
Abstract : Zeolitic imidazolate framework (ZIF‐8, Zn(2‐meIm)2 ) and composites based on ZIF‐8 and alumina nanofibers (Nafen TM ), i.e. ZIF‐8/Nafen, were demonstrated to be efficient heterogeneous catalysts for the reaction of methanol with propylene oxide to produce propylene glycol methyl ether (PGME), which is a member of the family of glycol ether solvents used for a wide variety of consumer products and industrial applications. Both the reaction rate and the selectivity toward PGME were found to decrease with increasing crystal size of the ZIF‐8 material, which was related to the change in the number of basic sites and their accessibility. The investigation of ZIF‐8/Nafen composites revealed the dependence of their catalytic performance on the amount of the ZIF‐8 component. In particular, the activity was affected by the crystal size of the ZIF‐8 material and the nature of acid‐base sites in its framework. Abstract : On the way to higher efficiency : The catalytic performance of systems based on ZIF‐8 in the synthesis of propylene glycol methyl ether can be tuned by reshaping active sites via dimensional and concentration effects. The smaller crystal size of ZIF‐8, the higher the reaction rate and the yield of the product.